Teknik Showing Berbantuan Multi Media Kreatif untuk Meningkatkan Keterampilan Menulis Teks Narasi - Rosidah, Faiqotur (Jurnal Didaktika Pendidikan Dasar, 2021)
This research on the learning technique using Showing assisted by creative multimedia is expected to be able to improve students’ narrative text writing skills at SMPN 3 Peterongan. The term Showing refers to two things, the first means show and the second means the acronym of the Survey stage, Hadiirkan Objek (Present Objects), Wujudkan (Realize), Imagine, Narrate, and Gaungkan (Reflect). This research is a learning development study with the 4D model developed by Thiagarajan, et al (1974) which consists of the stages of defining (conducting; analyzing needs), design (designing teaching materials with Showing techniques and validating teaching materials), developing (developing; testing) the use of instructional materials that have been designed), and disseminate (dissemination; the implementation of learning in the classroom that has been the subject of research). The subjects of this study were four classes, namely classes 7I and 7J and classes 9D and 9E. The total number of research subjects was 129 students. The results of this study are 97% of students are successful on a group basis, whereas 95% successful in the individual aspect.